Exploring Classroom Management In Teaching And Learning English: Case Study At Aekhayuara Islamic Boarding School Sibuhuan North Sumatera - Lijah Adena Hasibuan; Mutia Nasution; Linda Efrina Nasution (Wahana Didaktika : Jurnal Ilmu Kependidikan, 2023)
The aim of this study is to describe the classroom management practiced by English teachers during their teaching in Aek Hayuara Islamic Boarding School and to investigate the factors affecting the classroom management teaching process. This study was carried out with a qualitative research design. Participants of this study were eighth grade English teachers at an Islamic secondary school, Aek Hayuara Sibuhuan North Sumatera. Data were collected through observation and interviews. Observations and semi-structured interviews were used to collect data on classroom management.Education researchers work to understand the actual classroom management process. Data reduction, data presentation and data analysis methods using data result. In this study, the diversification method was used to evaluate the validity of the data. The research findings are as follows: (1) English teachers at Aek Hayuara Sibuhuan Islamic Junior Boarding School conduct classroom management in English. (2) However, the researchers found that not all aspects of classroom management are used by English teachers.(4) It has been shown that there are some effects on classroom management in English teaching; lack of accommodation, overcrowded classrooms, teacher planning and preparation, and classroom discipline. Through this study, the researchers suggest that all English teachers should be able to learn classroom management strategies in the teaching process because the learning process can be improved by using classroom management strategies.